Diagnostics of psychoemotional readiness for competitive activities of young basketball players - Kremneva, V. N.; Solodovnik, E. M. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assess the level of personal anxiety, self-esteem and the state of mental reliability of young basketball players.